Peningkatan Mutu Pelayanan Posyandu melalui Optimalisasi Peran Kader dan Masyarakat di Desa Cemplang, Serang, Banten - Tri Yulvia, Novrita; Nurhayati, Septi; Septiyani, Risti; Pratiwi, Amanda; Wasi, M. Arya Faizul; Suwito, Putri Amelia; Defiana, Risky; Maidila, Nia; Hudaroh, Hudaroh; Putri, Rossa Amelinda (IMPACT: Journal of Community Service, 2025)
Posyandu is one of the key pillars of primary healthcare services at the village level; however, its effectiveness is often hindered by limited skills among health cadres and low community participation. This community service program aimed to improve the quality of Posyandu services through health education, technical training for cadres, and the implementation of collaborative Posyandu activities in Cemplang Village, Serang Regency. The activities involved university students participating in a community service program (KKM), Posyandu cadres, public health center (Puskesmas) staff, village officials, and local residents. Evaluation was carried out using pre-tests and post-tests with six cadres and 20 residents, as well as by observing community participation. The results showed an increase in cadres’ knowledge scores from 68 to 92 (35.3%) and in community members’ scores from 54 to 85 (57.4%). In addition, visits by toddlers to the Posyandu increased by approximately 40% compared to the previous average. These findings indicate that collaborative interventions, interactive education, and hands-on practice can enhance cadres’ skills, improve community knowledge, and boost participation in healthcare services. This model has the potential to be replicated in other areas with cross-sectoral support.